Chemical-free and synergistic interaction of ultrasound combined with plasma-activated water (PAW) to enhance microbial inactivation in chicken meat and skin - Tanitta Royintarat (2020)
© 2020, The Author(s). In general, the poultry industry uses 0.5–1 ppm chlorine solution in the meat sanitization process. However, chlorine can react with organic material and produce halogenated organic compounds, notably chloroform, which causes bladder and rectal cancer in humans. For this reason, many industries try to avoid chlorine. This study investigated the efficacy of ultrasound and plasma-activated water (PAW) on the inactivation of Escherichia coli and Staphylococcus aureus in chicken muscle, rough skin, and smooth skin. Samples inoculated with bacteria suspension were treated by ultrasound alone and PAW–ultrasound. The Taguchi method and desirability function approach were used for the experimental design and optimization. Combined ultrasound and PAW inactivated up to 1.33 log CFU/ml of E. coli K12 and 0.83 log CFU/ml of S. aureus at a sample thickness of 4 mm, at 40 °C for 60 min, while PAW alone only reduced E. coli K12 by 0.46 log CFU/ml and S. aureus by 0.33 log CFU/ml under the same condition. The muscle topography showed a porous structure, which facilitated the penetration of PAW. The color measurements of muscle treated with ultrasound and PAW–ultrasound were dramatically different from the untreated sample, as also perceived by the sensory evaluation panel. Therefore, the synergistic interaction of combined PAW–ultrasound could be used to enhance microbial inactivation in meat.